Kontribusi Ekonomi Hasil Hutan Bukan Kayu (HHBK) Jambu Mete Terhadap Pendapatan Keluarga Petani di Desa Sillu Kecamatan Fatuleu Kabupaten Kupang - Trison Meiwilson Heri; Nixon Rammang; Norman P. L. B. Riwu Kaho (Wana Lestari, 2025)
This research was conducted in Sillu Village, Fatuleu District, Kupang Regency. The objective of the study was to determine the income generated from Non-Timber Forest Products (NTFP), specifically cashew nuts, and its contribution to the total household income of farmers in the village. The research location was selected using purposive sampling, while the respondents were selected randomly using the Slovin formula, with a total sample size of 75 farmers. The research employed a survey method. Data analysis used both qualitative and quantitative descriptive approaches. The data were processed using cost analysis, income analysis, and contribution analysis of the farming business.The results showed that cashew farming contributed 81,43% to the total farmer household income, amounting to IDR 372,775,000. Other agricultural activities contributed 8,75% (IDR 40,073,000), while non-agricultural activities contributed 9.82% (IDR 44,950,000). These findings indicate that cashew farming makes a significant contribution to the total household income of farmers compared to other sources of income.On average, cashew nut production per farmer in Sillu Village reached 189.44 kg per year, with total production amounting to 14,208 kg. However, most farmers remain at a low production level (approximately 100 kg per year). The average revenue from cashew farming per farmer was IDR 5,155,733 per year, with a net income of IDR 4,970,333 per year. Thus, cashew nuts represent the main source of income for farmers in Sillu Village.